Optimisation of Distribution Routes: A Case Study - Rudolf Kampf; Martina Hlatká; Patrik Gross (Communications - Scientific letters of the University of Zilina, 2021)
This article focuses on optimisation of the distribution routes for a company that produces carpets, floor coverings and tapestries. The optimisation process is based on operational research methods including, without limitations, Mayer’s method and the single linkage method. The obtained results are subsequently compared to the current situation and evaluated in terms of time and costs. The conclusion provides the optimised economic solution.